KAJIAN ETNOBOTANI MASYARAKAT KAMPUNG ADAT DUKUH KABUPATEN GARUT, JAWA BARAT - Sopian Hidayat; Agus Hikmat; Ervizal A.M. Zuhud (Media Konservasi, 2010)
The people of Dukuh Cultural Village Garut Regency, West Java are a group of community who live in traditional life pattern, respect the culture and tradition of their ancestor and stay in simply way. The usage of plants traditionally by local people is decrease keep pace with the modern development. This condition may occur to the people of Dukuh Cultural Village. Therefore the study concerning the ethnobotany of local people at Dukuh Cultural Village should be done. This study was the early documentation of indigenous knowledge of Dukuh Cultural Village  people. It is hopefully the result can be delivered and developed by young generation of Dukuh Cultural Village and people in general. The villagers’ lifestyle in Dukuh Cultural Village that is synergy to the nature should be maintained well in order to keep sustainable environmental and give benefit to social life.     Keywords: ethnobotany, indigenous knowledge, environmental, and Dukuh Cultural Village